5S route for safety management. (2016) - Ramesh, Nagarajan; Ravi, A.
This article describes a research study conducted to examine the methodology adopted to achieve the safety sustainability at the organisation level. 5S is a systematic technique used by organisations; it comes from five Japanese words; Seiri (sort), Seiton (set in order), Seiso (shine), Seiketsu (standardise), and Shitsuke (sustain). This system helps to organise a workplace for efficiency and decrease waste. One of the very important aspects of today's organisation is to ensure and provide a safe workplace to their employees. This can be achieved only through the participation of all the employees of the organisation. This paper aims to understand the 5S practices of the leading cutting tool manufacturing company and how a safety system was incorporated within their organisation. The results of this research showed a strong relationship between 5S technique implementation and safety performance of the organisation. The results show that 5S is an effective tool for improvement of organisation's safety performance.